The Impact of Food Inflation on Poverty in Nepal - Shrestha, Min Bahadur; Chaudhary, Shashi Kant (NRB Economic Review, 2012)
This paper examines the impact of food price hike on poverty in Nepal employing crosssectional sample household consumption data of Nepal Living Standard Survey III. The findings of the study suggest that a 10 percent rise in food prices is likely to increase overall poverty in Nepal by 4 percentage points. It implies that one percent rise in food inflation will push 100 thousand additional people into overall poverty and 180 thousand additional people into food poverty. The paper also analyses the impact at the regional level and suggests some policy options to contain the food inflation and to mitigate the impact of food price hike on the poor section of the population.